Social Entrepreneurship and its Impact on Sustainable Development Goals (SDGs) - Lindayani, Lindayani; Soni, Muhamad; Solihat, Asri (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
The challenges in implementing social entrepreneurship cannot be ignored. One significant barrier is the lack of understanding of the synergies and trade-offs between the various SDGs. Social and cultural barriers that can hinder the success of women entrepreneurs, especially in areas with strict traditional norms. The purpose of this study is to analyze the role of social entrepreneurship and its impact on sustainable development as an effort to explore opportunities to produce goods and services. The research method used is a case study is an approach commonly used in various disciplines, especially in the social and business fields, data collection techniques using in-depth interviews and observations that allow researchers to gain a more introspective and individual perspective, data analysis with triangulation includes observation, interviews and documentation studies. The results of this data analysis are that social entrepreneurship can have an impact on sustainable development with efforts to explore various social communities in improving skills in business but still have an impact in helping to create transparency and encourage community participation in sustainable development.